2017
DOI: 10.14475/kjhpc.2017.20.3.159
|View full text |Cite
|
Sign up to set email alerts
|

The Palliative Care and Hospice for the People Living with HIV

Abstract: According to the advance of antiretroviral regimen and the early treatment strategy, people living with human immunodeficiency virus (PLWH) are achieving the goal of virologic suppression and immune restoration. Most of them no more die of acquired immunodeficiency syndrome (AIDS) defining illnesses, and become older with chronic comorbidities such as cardiovascular, metabolic, hepatic, renal and neurological diseases. However some PLWH still visit hospitals as late presenters with very low CD4+ T cell counts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Considering South Korea’s extensive ART coverage, this proportion is alarming. These late presenters suffer from AIDS-defining illnesses and have a high risk of severe neurological complications resulting in disabilities [ 31 32 33 34 ]. Late presentation for HIV care is also a key marker of stigma manifestation: findings from a meta-analysis study identified that people who perceived high HIV-related stigma had twice the probability of late presentation than those who perceived low stigma [ 35 ].…”
Section: Challengesmentioning
confidence: 99%
“…Considering South Korea’s extensive ART coverage, this proportion is alarming. These late presenters suffer from AIDS-defining illnesses and have a high risk of severe neurological complications resulting in disabilities [ 31 32 33 34 ]. Late presentation for HIV care is also a key marker of stigma manifestation: findings from a meta-analysis study identified that people who perceived high HIV-related stigma had twice the probability of late presentation than those who perceived low stigma [ 35 ].…”
Section: Challengesmentioning
confidence: 99%